Life Cycle Analysis of Biodiesel Blends for Aviation - Rodríguez Delgado, William Evelio; Rodríguez Meléndez, Anderson Guillermo; Mayorga Betancourt, Manuel Alejandro; Bonilla Páez, Javier Alejandro; López Gómez, Mauricio (TECCIENCIA, 2020)
In the aviation sector, the use of biofuels has increased worldwide, therefore, this study assesses the environmental impact of these mass-based blends, named BK0, BK10, BK20 and BK30, according to their composition (Biodiesel + Kerosene) and the percentage of mass fraction. The study uses life cycle analysis with the SimaPro software and the Ecoinvent database for Colombia. The stages of cultivation, oil extraction and refining were established for biodiesel, while for the kerosene the stages defined were crude oil extraction and its refining. Results show that the stage with the greatest impact is the cultivation and extraction for both the category of freshwater ecotoxicity, acidification and terrestrial eutrophication.